Impact of Corporate Social Responsibility on OTC Medicines Consumers - Vasja Roblek; Andrej Bertoncelj (Amfiteatru Economic Journal, 2014)
In the article is presented the case of trust-based marketing of over-the-counter (OTC) medicines. The relationship between the hypotheses was tested by means of structural equation modelling. The results of the first model show that the predictor variable (consumer satisfaction with safety and information) has a significant effect on the mediator variable (consumer trust). The results of the second model show that the consumer trust also has a significant effect on virtual brand loyalty (dependent variable). Model 3 was developed by including consumer perception of corporate social responsibility (CSR) and consumer trust as independent predictor variables and virtual brand loyalty as the mediator variable with the specific intention to determine whether the effects of consumer perception of CSR on virtual brand loyalty became insignificant or less significant. The results of Model 3 show a partial mediator effect of consumer trust regarding the relationship between consumer perception of CSR and virtual brand loyalty.
Keywords: D12; L51; M14; M15; M38; 330; Consumer trust; corporate social responsibility; structural equation modelling; OTC medicines; social media; marketing; pharmaceutical companies